Diagrammatic iconicity in idiomatic expressions: a Chinese/French comparison (Signifiances (Signifying), 2024)
Idiomatic expressions (hereafter IE) are often considered arbitrary. Nevertheless, their non-arbitrariness is supported at semantic level, especially by semantic-cognitive research, but also at structural level. This study investigates the orle of semantic constraints in the ordering of three types of “binomial” constituents in IEs: numerical, spatial, and temporal, through a comparative analysis of French and Chines, two languages that are typologically and culturally distant. Relying primarily on the work of Cooper and Ross (1975) and Tang (1988), we investigate the extent to which these orders might reflect diagrammatic iconicity.